2017
DOI: 10.1021/acs.cgd.7b00597
|View full text |Cite
|
Sign up to set email alerts
|

Zinc(II)-Directed Self-Assembly of Metal–Organic Nanocapsules

Abstract: A metal−organic nanocapsule consisting of 24 Zn 2+ ions and six pyrogallol[4]arene units has been synthesized and structurally characterized. All the Zn 2+ ions seaming the nanocapsule are disordered over two positions forming concave distortions on the framework.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
15
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 29 publications
(39 reference statements)
3
15
0
Order By: Relevance
“…In that work, retroinsertion of 24 Cu 2+ ions in the framework of hydrogen‐bonded hexameric capsule resulted in substitution of 48 of the 72 phenolic protons involved in hydrogen bonding to yield a structure supported in part by 96 O→Cu coordinate bonds and 24 intramolecular hydrogen bonds. This trend was also observed in other M 24 L 6 systems that contained M 2+ ions . The X‐ray diffraction structural study revealed that the In 3+ /PgC5 hexameric MONC is a charge neutral capsule.…”
Section: Figuresupporting
confidence: 65%
See 1 more Smart Citation
“…In that work, retroinsertion of 24 Cu 2+ ions in the framework of hydrogen‐bonded hexameric capsule resulted in substitution of 48 of the 72 phenolic protons involved in hydrogen bonding to yield a structure supported in part by 96 O→Cu coordinate bonds and 24 intramolecular hydrogen bonds. This trend was also observed in other M 24 L 6 systems that contained M 2+ ions . The X‐ray diffraction structural study revealed that the In 3+ /PgC5 hexameric MONC is a charge neutral capsule.…”
Section: Figuresupporting
confidence: 65%
“…Peculiarly, these distinctive chemical environments on the upper and lower rims of the PgC n macrocycle impart to it the ability to generate metal‐seamed hexameric supramolecular capsules wherein 6 PgC n units are seamed together by 24 metal ions (M 24 L 6 ). This M 24 L 6 coordination geometry is evident from previous successful attempts to assemble hexameric MONCs based on the metals ions Cu, Ga, Co, Mg, Ni, Zn, and Mn …”
Section: Figurementioning
confidence: 71%
“…Interestingly, the overall metal-organic arrangement of this nanocapsule is strikingly similar to that of the previously reported Zn II -seamed analog. 36 On the basis of both bond-valence sum (BVS) analysis 42 and inspection of the Mn-O bond distances, all of the constituent Mn ions in 1 were determined to be in the 2+ oxidation state (Table S1). These Mn II ions are disordered over two positions, in-and out of the plane of the nanocapsule surface, and they all display distorted square pyramidal geometry by coordination to four equatorial phenolic oxygen atoms and an axial aqua ligand (Figure 2b).…”
Section: X-ray Crystallographic Analysis Of Nanocapsules 1 Andmentioning
confidence: 99%
“…[15][16][17][18][19][20][21][22][23][24][25][26][27] In recent times our research has focused on the metal-directed assembly of C-alkylpyrogallol [4]arenes (PgCn, where n is the number of carbon atoms in the pendant alkyl chains). 15,[28][29][30][31][32][33][34][35][36][37] PgCns are bowl-shaped polyphenols and, upon deprotonation, their upper-rim phenolic groups may coordinate to appropriate metal ions, leading to the formation of metal-organic nanocapsules (MONCs). 15,[28][29][30][31][33][34][35][36][37][38] MONCs are primarily self-assembled into two different structural forms, hexamers and dimers.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation